Association of neutrophil-to-lymphocyte ratio with severe abdominal aortic calcification: new evidence from the United States - Deng, Hao; Sun, Mengmeng; Zhao, Zhentong; Fan, Kun; Zhao, Zizhang; Chi, Yifan; Sheng, Wei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAbdominal aortic calcification (AAC), an early indicator of abdominal aortic wall atherosclerosis, is a marker of subclinical atherosclerosis and a predictive factor for vascular-associated morbidity and mortality. These outcomes are driven by inflammatory processes. Given the pivotal role of inflammatory mediators in the pathogenesis of aortic calcification, inflammation has attracted interest as a peripheral biomarker for early mortality prediction in patients with aortic calcification. The neutrophil-to-lymphocyte ratio (NLR) measured in the peripheral blood typically reflects the body's inflammatory response by combining laboratory markers of innate and adaptive immunity. The NLR is associated with the prognosis of a range of diseases, including circulatory, infectious, psychiatric, and neoplastic conditions. However, the precise relationship between the NLR and vascular calcification remains unclear. Therefore, the present study investigated the correlation between the NLR and AAC in a nationally representative sample from the US.MethodsThis study analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2013–2014. Multivariable logistic regression, stratified analysis with interaction, and restricted cubic spline analysis were used to examine the relationship between the NLR and AAC.ResultsThis study enrolled 3,047 participants [1,469 men (48.2%) and 1,578 women (51.8%)]. After adjusting for all covariates in the multivariate logistic regression, an independent association was identified between augmented NLR and the incidence of severe AAC (SAAC). The risk of SAAC increased by 8% with every 1% increase in NLR. Compared with the lowest NLR group [quartile 1 (Q1), <1.64], the adjusted odds ratio values for NLR and SAAC in Q3 (>2.34) were 1.42 (95% confidence interval: 1.02–1.96, p = 0.037), respectively. The results of subgroup analyses revealed no significant interaction effects.ConclusionsThe NLR was positively correlated with SAAC prevalence among adults in the US. These findings have significant clinical relevance and may inform clinicians regarding the management of SAAC. However, further research is required to confirm this association.